Culture Jamming Versus Popular Culture - Leonardia Acynthia Putri (Jurnal ILMU KOMUNIKASI, 2011)
Abstract: This literature study researched Adbusters, the anti-commercial organization, and described the organizationâ€™s activities and media usage, mainly in the period of 2007-2010, which critized the populer culture. Adbusters is an organization which performs â€œCulture Jammingâ€; a rebellious act reacting towards commercialism domination in many aspects including popular culture. Compared to other similar organizations, Adbusters has been executing more various activisms using several media which other organizations do not use. This study used the Adbustersâ€™ official website and blogs as main data sources. The data of Adbustersâ€™ activities and media usage were categorized and analyzed, thus the tendency of its development can be described. This study also analyzed Adbustersâ€™ activity using Media Hegemony Theory and Political Economy Media Theory. The media has been dominated by a certain group that owns politic and economic power, so the information flow has been dominated by them. Media and its contents have been commercialized, thus capitalism and commercialism have been considered as a common system that should run the world. Adbusters has been trying to stop the domination and change the societyâ€™s way of thinking into a more critical way of thinking.Â Abstrak: Studi literatur ini meneliti tentang Adbusters, sebuah organisasi anti komersial, dengan mendeskripsikan aktivitas serta penggunaan media organisasi tersebut dari tahun 2007-2010 dalam mengkritisi budaya populer. Adbusters adalah organisasi yang melakukan Culture Jamming, aksi perlawanan terhadap dominasi komersialisme di segala aspek termasuk popular culture. Dibandingkan dengan organisasi lain yang serupa, aktivitas Adbusters lebih bervariasi dan menggunakan media-media yang tidak biasa digunakan organisasi lain. Penelitian ini menggunakan situs online resmi Adbusters sebagai sumber data utama. Data mengenai aktivitas dan penggunaan media Adbusters dikategorisasi dan dianalisis sehingga kecenderungan perkembangan organisasi ini dapat dideskripsikan. Penelitian ini juga menganalisis kegiatan Adbusters menggunakan Teori Hegemoni Media dan Teori Media Ekonomi Politik. Media telah didominasi oleh kelompok tertentu yang memiliki kekuasaan ekonomi serta politik, sehingga alur informasi juga didominasi kelompok tersebut. Media dan kontennya telah menjadi produk komersial, sehingga kapitalisme dan komersialisme itu sendiri dianggap sebagai sistem yang memang sudah seharusnya dijalankan di dunia. Adbusters berusaha menghentikan dominasi tersebut dan mengubah cara pikir masyarakat menjadi lebih kritis.